An improved synthesis of poly(amidoamine)s for complexation with self-amplifying RNA and effective transfection - Gurnani,P; Blakney,AK; Yeow,J; Bouton,CR; Shattock,RJ; Stevens,MM; Alexander,C (Polymer Chemistry, 2020)
Cationic polymers are widely used as materials to condense nucleic acids for gene-based therapies. These have been developed to mainly deliver DNA and RNA for cancer therapies but the ongoing COVID-19 pandemic has demonstrated an urgent need for new DNA and RNA vaccines. Given this, suitable manufacturing conditions for such cationic polymers which can protect the nucleic acid in the formulation and delivery stages but release the cargo in the correct cellular compartment effectively and safely are required. A number of polymers based on poly(amidoamine)s fit these criteria but their syntheses can be time-consuming, inefficient and poorly reproducible, precluding their adoption as manufacturable vaccine excipients. Here we report an improved synthesis of poly(cystamine bisacrylamide-co-4-amino-1-butanol), abbreviated as pABOL, via modifications in concentration, reaction time and reaction conditions. Optimisation of monomer contents and stoichiometries, solvents, diluents and temperature, combined with the application of microwaves, enabled the preparation of vaccine candidate pABOL materials in 4 h compared to 48 h reported for previous syntheses. These procedures were highly reproducible in multiple repeat syntheses. Transfection experiments with a model RNA showed that polymers of formulation with appropriate molar masses and mass distributions were as effective in model cell lines as polymers derived from the unoptimised syntheses which have been shown to have high efficacy as RNA vaccine formulation candidates.